Synthesis and biological evaluation of quinoxaline di-N-oxide derivatives with in vitro trypanocidal activity. Issue 3 (1st February 2016) - Pérez-Silanes, Silvia; Torres, Enrique; Arbillaga, Leire; Varela, Javier; Cerecetto, Hugo; González, Mercedes; Azqueta, Amaya; Moreno-Viguri, Elsa
Graphical abstract: Abstract: We report the synthesis and in vitro activity against Trypanosoma cruzi epimastigotes of 15 novel quinoxaline derivatives. Ten of the derivatives presented IC50 values lower than the reference drugs Nfx and Bzn; four of them standed out with IC50 values lower than 1.5 μM. Moreover, unspecific cytotoxicity and genotoxicity studies are also reported. Compound14 showed a SI higher than 24, whereas compound10 was the only one that was negative in the genotoxicity screening.